Implementasi Prinsip Ekonomi Islam dalam Asuransi Syariah di Indonesia - Deasy Eka Saputri; Muhamad Hidayat Nurwahid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the implementation of Islamic economic principles in Islamic insurance (takaful) in Indonesia, focusing on principles such as justice, benefit, balance, and universality. Islamic insurance differs from conventional insurance as it is based on principles of mutual assistance and avoids riba (usury), maysir (gambling), and gharar (uncertainty). This research also discusses the differences between Islamic and conventional insurance, including the claims mechanism and the products offered by Islamic insurance companies in Indonesia. The study aims to contribute to the development of the Islamic insurance industry in Indonesia and provide a better understanding of how Islamic economic principles are applied in the practice of Islamic insurance.